Questions of reliability of surface fitting methods - Herczeg, Ádám (Acta Agraria Kaposváriensis, 2010)
In this paper the analysation of some popular GIS surface fitting method are examined. Some results collected from analyzation of the residuals between a model data set and its fitted data are also shown. Examination of the correctness of various 2D fitting methods on a field data set was performed. This is a short review of using and setting computerized surface fitting techniques.